Prosedur Falsanella-Servat pada pada ptosis traumatika: laporan kasus - Rima Febry Lesmana; Anak Agung Ayu Sukartini Djelantik; Putu Yuliawati; Ni Made Laksmi Utari; I Made Agus Kusumadjaja (DiscoverSys Inc., 2021)
Background : Ptosis is a drooping or infero displacement of the upper eyelid. Traumatic Ptosis is the second most common type after acquired aponeurotic ptosis. In this case the patient with mild traumatic ptosis had no improvement for 1 year. Surgery was performed for correction of traumatc ptosis with falsanella servat procedure. The aims of case report are to know managament patient with mild traumatic ptosis who underwent surgery with falsanella-servat procedure.Case presentation: A 18-year-old boy with dropping of left upper eyelid since 1 year ago. He had a history of hordeolum and had a curettage incision for three times. Complete opthalmology examination was perfomed on both eyes and found on right eyelid vertical palpebra fissure 12mm, horizontal palpebra fissure 35mm, levator action 18, margin limbal distance 9, margin reflect distance 4, lid crease 8, no lidlag, positive bell's phenomenon. Left eyelid examination results 8mm vertical palpebra fissure, 35mm horizontal palpebra fissure, levator action 16, margin limbal distance 7, margin reflect distance 2, lid crease 10, no lid lag, positive bell's phenomenon. Correction of traumatic ptosis with falsanella servat was performed and ptosis measurement had done after correction. Conclusion: Surgical procedure using falsanella-servat on traumatic mild ptosis gives good contour, functional and cosmetic results. Latar belakang: Ptosis adalah penurunan kelopak mata atas dari posisi normal. Ptosis traumatika merupakan kejadian tersering kedua setelah acquired aponeurotic ptosis. Pada kasus ini pasien dengan mild ptosis traumatika yang tidak mengalami perbaikan selama 1 tahun, dilakukan pembedahan dengan teknik operasi falsanell-servat. Tujuan dari penelitian ini adalah untuk melaporkan hasil penatalaksanaan pada pasien dengan mild ptotis traumatika yang dilakukan prosedur terapi dengan tekhnik falsanella-servat.Laporan kasus: Pasien laki-laki 18 tahun dengan penurunan kelopak atas mata kiri sejak 1 tahun yang lalu. Pasien riwayat hordeolum pada kelopak atas mata kiri dan sempat di insisi-kuretase sebanyak 3x. Pemeriksaan mata lengkap dilakukan pada kedua mata dan didapatkan kelopak mata kanan fisura palpebra vertikal 12mm, fisura palpebra horisontal 35mm, levator action 18, margin limbal distance 9, margin reflect distance 4, lid crease 8, lid lag tidak ada, bell’s phenomenon positif. Hasil pemeriksaan kelopak mata kiri didapatkan fisura palpebra vertikal 8mm, fisura palpebra horisontal 35mm, levator action 16, margin limbal distance 7, margin reflect distance 2, lid crease 10, lid lag tidak ada, bell’s phenomenon positif. Pasien dilakukan perbaikan ptosis traumatika dengan tekhnik pembedahan falsanella-servat dan pengukuran ptosis setelah perbaikan.Simpulan: Prosedur pembedahan dengan Falsanella-servat pada mild ptosis traumatika memberikan hasil yang baik dalam segi kontur, fungsi dan kosmetik.